Correlation of Esophageal Lengths with Measurable External Parameters - Song, Tae Jin (Korean J Intern Med, 1991)
Previous data for esophageal lengths are based on age related groups or cadaveric examination, both of which are improper for application to various individualized procedures. Because of the variability in height for any given age and longer length in vivo, lindividualized approximation is needed. Thus, we measured various anatomical levels of the esophagus using a flexible endoscope and correlated these data with measurable external body intervals. The mean esophageal length was 40.92±2.79, which is longer than the length derived from cadaveric examinations. Also, esophageal lengths which correlated better with height than any other body intervals, could be calculated from the following equation. Esophageal length from the upper incisors to the esophagogastric junction (L) can be expressed: L = 0.242 × height (Ht) + 2.078cm (P = 0.000, R(2) = 0525). The data from our study indicate that esophageal length can be reliably predicted using external body parameters before employing various procedures.